2000
DOI: 10.1118/1.599010
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a 41×41‐cm amorphous silicon flat panel x‐ray detector for radiographic imaging applications

Abstract: We report the performance of a 41 X 41-cm2 amorphous silicon-based flat panel detector designed for radiographic imaging applications. The detector consists of an array of photodiodes and thin film transistor switches on a 0.2-mm pitch with an overlying thallium-doped cesium iodide scintillator. The performance of the detector was evaluated through measurement of the frequency-dependent detective quantum efficiency [DQE(f)]. Measurements of the characteristic curve and modulation transfer function (MTF) are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(120 citation statements)
references
References 27 publications
1
119
0
Order By: Relevance
“…This arm allows the detector to be positioned at source to electronic portal imaging device (EPID) distance of 160 cm with an active imaging area of 41 × 41 cm 9. The image matrix is created from an array of 1024 × 1024 photodiodes with a pitch of 400 μm 10. While the EPID can be operated in various acquisition modes, a single exposure, 6 MV planar radiographic mode was used in this study.…”
Section: Materials/methodsmentioning
confidence: 99%
“…This arm allows the detector to be positioned at source to electronic portal imaging device (EPID) distance of 160 cm with an active imaging area of 41 × 41 cm 9. The image matrix is created from an array of 1024 × 1024 photodiodes with a pitch of 400 μm 10. While the EPID can be operated in various acquisition modes, a single exposure, 6 MV planar radiographic mode was used in this study.…”
Section: Materials/methodsmentioning
confidence: 99%
“…Other detector properties have been described extensively in the literature. 6,16 A standard MX 100 x-ray tube insert and housing (GE Healthcare, Waukesha, WI) were used with an ULTRANET SA beam collimator (Medys, Monza, Italy). The system source to image distance (SID) was 186 cm.…”
Section: Iib1 Imaging Systemmentioning
confidence: 99%
“…4,5 Examples from digital radiography have also shown that 2D undersampling and aliasing effects are important to consider, especially in calculations of noise equivalent quanta (NEQ) and detective quantum efficiency (DQE). [6][7][8] Complete assessments of the 2D NEQ and DQE are valuable in assessments of observer task performance since image interpretation is an inherently 2D task. 5 And although the 2D noise power spectrum (NPS) is easily measured, regular evaluations of the full 2D NEQ and DQE have been difficult due to various challenges in obtaining accurate estimates of the 2D MTF.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [15][16][17][18][19][20][21][22][23][24] have shown that FP detectors developed for use in general radiography have a significantly higher detective quantum efficiency (DQE) than both SF and CR systems. This higher DQE may lead to a better low contrast performance that should be evaluated and investigated with reception studies.…”
Section: Mammographymentioning
confidence: 99%